2017
DOI: 10.3892/mmr.2017.7841
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin ameliorates myocardial apoptosis by suppressing endoplasmic reticulum stress in rats with long‑term diabetic cardiomyopathy

Abstract: The effects of melatonin (MLT), which exerts cardioprotective effects against myocardial apoptosis, in long‑term diabetic cardiomyopathy are not currently well defined. The present study aimed to investigate how MLT protects the heart through modulating myocardial apoptosis in rats with type 2 diabetes mellitus (DM). In total, 36 rats were randomly divided into three groups, including control (n=12), DM (n=12) and DM + MLT (n=12) groups. The results demonstrated that, in DM rats, a significant increase was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…Activation of PGC1α-SIRT3 signaling plays a key role in cardioprotective action of melatonin; this signaling pathway leads to the enhancement of mitochondrial SOD activity, oxidative phosphorylation of Complexes I, III and IV, and reduction of mitochondrial lipid peroxidation, ROS generation and myocardial apoptosis [79]. In addition, it has been emphasized that melatonin treatment ameliorates myocardial apoptosis through suppressing ER-stress and spleen tyrosine kinase (Syk)/mitochondrial complex I/sarcoendoplasmic reticulum calcium transport ATPase (SERCA) axis [82,83]. Chronic high-glucose activates Syk leading to the repression of the expression and activity of mitochondrial complex I causing increased generation of ROS and subsequent peroxidation of SERCA; this results in the inhibition of cytoplasmic calcium re-uptake by ER leading to cellular calcium overload and cardiomyocytes death via activation of mitochondria-and ER stress-mediated apoptosis [82,83].…”
Section: Effects Of Melatonin On Diabetic Cardiomyopathymentioning
confidence: 99%
“…Activation of PGC1α-SIRT3 signaling plays a key role in cardioprotective action of melatonin; this signaling pathway leads to the enhancement of mitochondrial SOD activity, oxidative phosphorylation of Complexes I, III and IV, and reduction of mitochondrial lipid peroxidation, ROS generation and myocardial apoptosis [79]. In addition, it has been emphasized that melatonin treatment ameliorates myocardial apoptosis through suppressing ER-stress and spleen tyrosine kinase (Syk)/mitochondrial complex I/sarcoendoplasmic reticulum calcium transport ATPase (SERCA) axis [82,83]. Chronic high-glucose activates Syk leading to the repression of the expression and activity of mitochondrial complex I causing increased generation of ROS and subsequent peroxidation of SERCA; this results in the inhibition of cytoplasmic calcium re-uptake by ER leading to cellular calcium overload and cardiomyocytes death via activation of mitochondria-and ER stress-mediated apoptosis [82,83].…”
Section: Effects Of Melatonin On Diabetic Cardiomyopathymentioning
confidence: 99%
“…In a Zucker diabetic fatty rat model, which has a higher initial weight and weight gain, melatonin showed lipid homeostasis regulation in the context of obesity and hyperglycemia [120]. Additionally, melatonin exerts benefits in other hyperglycemia-induced pathological models, including cardiac apoptosis [121], myocardial I/R injury [122], cardiac fibrosis [123], and retinopathy [124]. These findings further confirm the atheroprotective benefits of melatonin in the context of hyperglycemia.…”
Section: Hyperglycemiamentioning
confidence: 53%
“…It also published that melatonin could protect the rat heart against diabetesinduced apoptosis through ameliorating metabolic risk factors and modulating apoptotic proteins [43]. Our former research also revealed that melatonin played a positive role against the apoptosis via regulating endoplasmic reticulum stress and MAPK pathways [27,28]. In this study, our data showed that melatonin could not directly decrease blood glucose level in diabetic rats, but it could distinctly ameliorate diabetic cardiac dysfunction independent of regulation of blood glucose level, perhaps partly through reducing myocardial apoptosis via modulation of MAPK signal pathways and apoptosis-related proteins.…”
Section: Discussionmentioning
confidence: 69%
“…Ding et al elucidated that melatonin participated in preventing Drp1-mediated mitochondrial ssion by regulating SIRT1-PGC1α pathway [26]. In our previous research, melatonin not only prevented diabetic cardiomyocyte apoptosis via inhibiting endoplasmic reticulum stress, but also ameliorated diabetic arterial endothelial permeability by regulating MAPK signaling pathway activation [27,28]. Intriguingly, previous studies have demonstrated the intimate relationship between cardiomyocyte apoptosis and MAPK signal pathways.…”
mentioning
confidence: 85%